LncRNA NEAT1 Sponges MiRNA-148a-3p to Suppress Choroidal Neovascularization and M2 macrophage polarization. (November 2020) - Zhang, Pengfei; Lu, Bing; Zhang, Qi; Xu, Fengyuan; Zhang, Rongrong; Wang, Chen; Liu, Yinping; Wei, Chenghua; Mei, Lixin
Highlights: LncRNA NEAT1 sponges miRNA-148a-3p to modulate M1/M2 macrophage polarization. Inhibition of lncRNA NEAT1 could suppress M2-type macrophage polarization. This study first reports inhibition of lncRNA NEAT1 could suppress CNV formation in a mice model. Abstract: Purpose: Long noncoding RNAs (lncRNAs) have emerged as essential regulators in many biological processes; however, little is known about the role of lncRNAs in choroidal neovascularization (CNV). The aim of this study was to investigate the role of lncRNA NEAT1 in CNV formation, and assessed whether inhibition of lncRNA NEAT1 could suppress M2-type macrophage polarization and CNV. Methods: The expression profiles of lncRNAs in a CNV mice model were accessed via microarray analysis. The role of lncRNA NEAT1 on macrophage polarization was assessed both in vitro and vivo. The interaction between lncRNA NEAT1, miR-148a-3p, and PTEN was assessed using a dual-luciferase reporter assay and RNA immunoprecipitation assay. Additionally, to evaluate the role of lncRNA NEAT1 on CNV development, eyes of mice in the mice CNV model were examined by Fluorescein Angiography (FA) and choroidal flatmounts on days 3 and 7 after intravitreal injection. Results: The results revealed that 128 lncRNAs were significantly altered in the RPE-choroid-sclera complexes of CNV mice ( P < 0.05, fold change > 2.0). Additionally, lncRNA NEAT1 increased in CNV formation and M2 macrophage polarization. LncRNA NEAT1 sponging miRNA-148a-3p targeting PTEN can modulate M2 macrophage polarization in mice CNV models as well as in bone marrow-derived macrophages cultured in vitro. Inhibition of lncRNA NEAT1 can suppress M2 macrophage both in vitro and vivo. Moreover, the intravitreal injection of a lncRNA NEAT1 Smart Silencer can inhibit CNV leakage and neovascularization. Conclusion: LncRNA NEAT1 via miRNA-148a-3p targeting PTEN plays a significant role in M2 macrophage polarization, while the inhibition of lncRNA NEAT1 can suppress choroidal neovascularization by inhibiting M2 macrophage polarization.